Climate change prevention through community actions and empowerment: a scoping review - Costa, Maria João Salvador (2022)
As society tries to tackle climate change around the globe, communities need to reduce its impact on human health. The purpose of this review is to identify key stakeholders involved in mitigating and adapting to climate change, as well as the type and characteristics of community empowerment actions implemented so far to address the problem. Published and unpublished studies from January 2005 to March 2022 in English and Portuguese were included in this review. The search, conducted on PubMed, CINAHL, Scopus, MEDLINE, Scopus, Web of Science, SciELO, and RCAAP (Repositório Científico de Acesso Aberto de Portugal), followed a three-step search strategy. Data extraction was performed by two independent reviewers, using an extraction tool specifically designed for the review questions. Twenty-seven studies were eligible for inclusion: six used interviews as a qualitative method, three were systematic reviews, three were case study analyses, three used surveys and questionnaires as quantitative methods, two used integrative baseline reviews, and three utilized a process model design. Six studies targeted local, public and private stakeholders. Community settings were the context target of fifteen studies, whereas twelve specifically referred to urban settings. Seven types of community actions were acknowledged across the globe, characterised as hybrid interventions and referring to the leading stakeholders: local governments, non-governmental organizations, civil society, universities, public health, and private sectors.